CITRAAN DALAM PERIBAHASA BANJAR - Siti Akbari (Universitas Lambung Mangkurat, 2020)
Abstract Imagery in the Banjarese Proverb. This is a descriptive qualitative research. This research was aimed at looking at Banjarese Proverb objectively. Therefore, this research focused on the proverbs that were obtained and then reviewed using semiotic analysis. The data used as the object this research were those in the form of Banjarese proverbs, which were derived from several informants and from reading material.The results showed that of the 147 proverbs collected, and there were sixty-two proverbs were found showed visual images. Twenty-three proverbs that show hearing images. Eight proverbs that show palpable imagery. Six proverbs that show olfactory images. Forty-eight proverbs that show the image of taste.The results showed that the choice of words became unique in the Banjar proverbs. The overall image strengthens the local area drawn from the Banjar proverb. This is evident from the choice of words in the Banjar proverb. Key words: image, proverbs, Banjar Abstrak Citraan dalam Peribahasa Banjar. Penelitian ini merupakan penelitian yang bersifat deskriptif kualitatif. Penelitian ini melihat peribahasa secara objektif. Oleh karena itu, penelitian ini fokus pada peribahasa yang diperoleh untuk kemudian ditelaah dengan menggunakan analisis semiotik. Adapun data dan sumber data yang dijadikan sebagai objek penelitian ini adalah data berupa peribahasa Banjar yang bersumber dari beberapa informan dan dari bahan bacaan. Hasil penelitian menunjukkan bahwa dari 147 peribahasa yang dikumpulkan, ditemukan enam puluh dua peribahasa yang menunjukkan citraan penglihatan. Dua puluh tiga peribahasa yang menunjukkan citraan pendengaran. Delapan peribahasa yang menunjukkan citraan perabaan. Enam peribahasa yang menunjukkan citraan penciuman. Empat puluh delapan peribahasa yang menunjukkan citraan pencecapan. Hasil penelitian menunjukkan bahwa pilihan kata menjadi kekhasan dalam peribahasa Banjar. Citraan secara keseluruhan menguatkan lokal kedaerahan yang tergambar dari peribahasa Banjar. Hal itu terbukti dari pilihan kata yang ada di dalam peribahasa Banjar. Kata-kata kunci: citraan, peribahasa, Banjar